2017
DOI: 10.1002/celc.201700914
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of Li2S‐Loaded amphiphilic Porous Carbon and Modification of the Li2S Electrode for Long‐Life Li2S Batteries

Abstract: A strategy to construct amphiphilic inner surfaces with hydrophilic N, SÀO and CÀSÀC sites in porous carbon is presented for applications in Li 2 S batteries. The amphiphilic porous carbon (APC) with high wettability, specific surface area, and polysulfide (PS) absorption ability is obtained through the pyrolysis of a glucoseÀthiourea resin with a nano-CaCO 3 template. Furthermore, a Li 2 S-loaded APC is developed in which Li 2 SO 4 is employed instead of CaCO 3 . Li 2 SO 4 is not only a reactant for Li 2 S pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Lithium sulfide (Li 2 S) as an alternative Li-ion source for sulfur-based batteries has received considerable attention in the past years . However, the electronically insulating nature of chunky commercial Li 2 S particles results in an enormous first-charge overpotential and poor material utilization .…”
mentioning
confidence: 99%
“…Lithium sulfide (Li 2 S) as an alternative Li-ion source for sulfur-based batteries has received considerable attention in the past years . However, the electronically insulating nature of chunky commercial Li 2 S particles results in an enormous first-charge overpotential and poor material utilization .…”
mentioning
confidence: 99%
“…Li 2 S‐CGA shows a high Coulumbic efficiency, which can be attributed to the 3D‐connected carbon matrix of CGA. [ 62 ] The sharp comparison is that the Li 2 S‐CGA/CeO 2 possesses a smaller polarization level and a higher discharge specific capacity. More profoundly, Li 2 S‐CGA/CeO 2 composite electrode shows two stable discharge plateaus even at the high current of 2C.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al demonstrated this approach by creating a Li 2 S@APC precursor through spray-drying a Li 2 SO 4 -enhanced glucose-thiourea resin solution. 71 However, the resulting products were mostly distributed in micron sizes, and the Li 2 S particles were still relatively large. To address this issue, researchers integrated carbon nanotubes (CNT) into the polymer, successfully preventing the agglomeration of Li 2 S nanoparticles by introducing N, S, and O atoms as the LiPS-friendly active sites.…”
Section: S Engineeringmentioning
confidence: 99%